2020
DOI: 10.1007/s40519-020-00974-9
|View full text |Cite
|
Sign up to set email alerts
|

Implicit bias to food and body cues in eating disorders: a systematic review

Abstract: Background Rigid, restrictive eating patterns, fear of gaining weight, body image concerns, but also binge eating episodes with loss of control leading to overweight, at times followed by compensatory measures to control weight, are typical symptoms in eating disorders (EDs). The regulation of food intake in EDs may underlie explicit processes that require cognitive insight and conscious control or be steered by implicit mechanisms that are mostly automatic, rapid, and associated with affective-rather than cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 113 publications
(190 reference statements)
0
13
1
Order By: Relevance
“…Recently, several authors (e.g., Paslakis et al, 2016; Paslakis et al, 2020; Steinglass & Walsh, 2016; Uniacke et al, 2018; Walsh, 2013) suggested that automatic, or implicit, processes might be an important mechanism in the development and maintenance of eating disorders. It is assumed that a shift from goal‐directed to habitual behavior, as observed in addictive behaviors (Everitt & Robbins, 2016), might also be relevant in eating disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several authors (e.g., Paslakis et al, 2016; Paslakis et al, 2020; Steinglass & Walsh, 2016; Uniacke et al, 2018; Walsh, 2013) suggested that automatic, or implicit, processes might be an important mechanism in the development and maintenance of eating disorders. It is assumed that a shift from goal‐directed to habitual behavior, as observed in addictive behaviors (Everitt & Robbins, 2016), might also be relevant in eating disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Only recently, several authors suggested that automatic processes and a shift from goal‐directed to habitual behavior might be an important aspect in the development and maintenance of eating disorders (e.g., Paslakis et al, 2016; Paslakis, Scholz‐Hehn, Sommer, & Kühn, 2020; Steinglass & Walsh, 2016; Uniacke, Walsh, Foerde, & Steinglass, 2018; Walsh, 2013). Walsh (2013) hypothesized that disorder‐compatible stimuli (e.g., pictures of underweight bodies) trigger the mesolimbic reward system and promote restraint eating habits.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the available literature includes several examples of successful pairing procedures, including with clinical populations, related to improving negative self-concepts [15], body ideals [16], and food preferences [17]. Given the relevance of these and similar evaluations for the emergence and maintenance of disordered cognitions and behaviors [23][24][25][26][27][28][29][30][31][32][33], pairing procedures may indeed offer a simple yet effective means of complementing CBT.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this idea, an increasing number of studies show that altered evaluations link to disordered cognitions and behaviors. For example, a generalized negative self-evaluation, i.e., negative self-esteem, both characterizes and predicts the onset of depressive symptoms [23][24][25]; shifted evaluations of body ideals and foods are associated with the development and maintenance of eating disorders [26][27][28][29][30][31]; phobic patients show evaluative biases in processing fear-relevant stimuli and situations [32,33]. These and similar evaluations need not be consistent with an individual's explicit beliefs or goals (e.g., people frequently desire sweets despite knowing the benefits of restraint [34]) and are less susceptible to conscious introspection and control [19].…”
Section: The Clinical Potential Of Pairing Proceduresmentioning
confidence: 99%
“…The most common among them is the approach-avoidance task (AAT), which requires push or pull movements, mediated by a computer joystick, depending on whether the reaction is to avoid or to approach food pictures [7,9,[16][17][18][19]. AAT modi cation protocols are discussed as interventions in obesity and eating disorders, since they are hypothesized to overcome the low e cacy of conventional treatments by targeting early cognitive processing of food stimuli [16,20]. However, AAT modi cation studies did not always yield consistent results [21,22].…”
Section: Introductionmentioning
confidence: 99%